A model of chronic enthesitis and new bone formation characterized by multimodal imaging - Czegley, Christine; Gillmann, Clarissa; Schauer, Christine; Seyler, Lisa; Reinwald, Christiane; Hahn, Madelaine; Uder, Michael; Jochmann, Katja; Naschberger, Elisabeth; Stock, Michael; Schett, Georg; Bäuerle, Tobias; et al. (Disease Models & Mechanisms, 2018)
Enthesitis is a key feature of several different rheumatic diseases. Its pathophysiology is only partially known due to the lack of access to human tissue and the shortage of solid animal models for enthesitis. Here we aimed to develop a model, which mimics the effector phase of enthesitis and reliably leads to inflammation and new bone formation.Enthesitis was induced by local injection of monosodium urate crystals (MSU) into the metatarsal entheses of wild type (WT) or oxidative burst-deficient Ncf1** mice. Quantitative variables of inflammation (edema, swelling) and vascularization (tissue perfusion) were assessed by MRI, bone forming-activity by [18F]-fluoride-PET and destruction of cortical bone and new bone formation by CT. Non-invasive imaging was validated by histochemical and histomorphometric analysis.While injection of MSU crystals into WT mice triggered transient mild enthesitis with no new bone formation, Ncf1** mice developed chronic enthesitis accompanied by massive enthesiophytes. In MRI, inflammation and blood flow in the entheses were chronically increased while PET/CT showed osteoproliferation with enthesiophyte formation. Histochemical analyses showed chronic inflammation, increased vascularization, osteoclast differentiation and bone deposition in the affected entheseal sites.Herein we describe a fast and reliable effector model of chronic enthesitis, which is characterized by a combination of inflammation, vascularization and new bone formation. This model will help to disentangle the molecular pathways involved in the effector phase of enthesitis.
EVALuna2:34481

Characterization of the murine orthotopic adamantinomatous craniopharyngioma PDX model by MRI in correlation with histology - Hoelsken, Annett; Schwarz, Marc; Gillmann, Clarissa; Pfister, Christina; Uder, Michael; Dörfler, Arnd; Buchfelder, Michael; Schlaffer, Sven-Martin; Fahlbusch, Rudolf; Buslei, Rolf; Bäuerle, Tobias (PLoS ONE, 2018)
PURPOSE: Adamantinomatous craniopharyngiomas (ACP) as benign sellar brain tumors are challenging to treat. In order to develop robust in vivo drug testing methodology, the murine orthotopic craniopharyngioma model (PDX) was characterized by magnetic resonance imaging (MRI) and histology in xenografts from three patients (ACP1-3). METHODS: In ACP PDX, multiparametric MRI was conducted to assess morphologic characteristics such as contrast-enhancing tumor volume (CETV) as well as functional parameters from dynamic contrast-enhanced MRI (DCE-MRI) and diffusion-weighted imaging (DWI) including area-under-the-curve (AUC), peak enhancement (PE), time-to-peak (TTP) and apparent diffusion coefficient (ADC). These MRI parameters evaluated in 27 ACP PDX were correlated to histological features and percentage of vital tumor cell content. RESULTS: Qualitative analysis of MRI and histology from PDX revealed a similar phenotype as seen in patients, although the MRI appearance in mice resulted in a more solid tumor growth than in humans. CETV were significantly higher in ACP2 xenografts relative to ACP1 and ACP3 which correspond to respective average vitality of 41%, <10% and 26% determined histologically. Importantly, CETV prove tumor growth of ACP2 PDX as it significantly increases in longitudinal follow-up of 110 days. Furthermore, xenografts from ACP2 revealed a significantly higher AUC, PE and TTP in comparison to ACP3, and significantly increased ADC relative to ACP1 and ACP3 respectively. Overall, DCE-MRI and DWI can be used to distinguish vital from non-vital grafts, when using a cut off value of 15% for vital tumor cell content. CONCLUSIONS: MRI enables the assessment of craniopharyngioma PDX vitality in vivo as validated histologically.
EVALuna2:34588

Early Alterations in Operant Performance and Prominent Huntingtin Aggregation in a Congenic F344 Rat Line of the Classical CAGn51truncModel of Huntington Disease - Plank, Anne-Christine; Canneva, Fabio; Raber, Kerstin A.; Urbach, Yvonne K.; Dobner, Julia; Puchades, Maja; Bjaalie, Jan G.; Gillmann, Clarissa; Bäuerle, Tobias; Riess, Olaf; Nguyen, Hoa H. P.; von Hörsten, Stephan (Frontiers in Neuroscience, 2018)
The transgenic rat model of Huntington disease expressing a fragment of mutant HTT (tgHD rat) has been thoroughly characterized and reproduces hallmark symptoms of human adult-onset HD. Pursuing the optimization of this model for evaluation of translational therapeutic approaches, the F344 inbred rat strain was considered as advantageous genetic background for the expression of the HD transgenic construct. In the present study, a novel congenic line of the SPRDtgHD transgenic model of HD, carrying 51 CAG repeats, was generated on the F344 rat genetic background. To assess the behavioral phenotype, classical assays investigating motor function, emotion, and sensorimotor gating were applied, along with automated screening of metabolic and activity parameters as well as operant conditioning tasks. The neuropathological phenotype was analyzed by immunohistochemistry andex vivomagnetic resonance imaging. F344tgHD rats displayed markedly reduced anxiety-like behavior in the social interaction test and elevated impulsivity traits already at 3 months of age. Neuropathologically, reduced striatal volume and pronounced aggregation of mutant huntingtin in several brain regions were detected at later disease stage. In conclusion, the congenic F344tgHD model reproduces key aspects of the human HD phenotype, substantiating its value for translational therapeutic approaches.
EVALuna2:32797

EGFL7 enhances surface expression of integrin α5β1 to promote angiogenesis in malignant brain tumors - Stankovic, Nevenka Dudvarski; Bicker, Frank; Keller, Stefanie; Jones, David T. W.; Harter, Patrick N.; Kienzle, Arne; Gillmann, Clarissa; Arnold, Philipp; Golebiewska, Anna; Keunen, Olivier; Giese, Alf; Von Deimling, Andreas; et al. (Embo Molecular Medicine, 2018)
Glioblastoma (GBM) is a typically lethal type of brain tumor with a median survival of 15 months postdiagnosis. This negative prognosis prompted the exploration of alternative treatment options. In particular, the reliance of GBM on angiogenesis triggered the development of anti-VEGF (vascular endothelial growth factor) blocking antibodies such as bevacizumab. Although its application in human GBM only increased progression-free periods but did not improve overall survival, physicians and researchers still utilize this treatment option due to the lack of adequate alternatives. In an attempt to improve the efficacy of anti-VEGF treatment, we explored the role of the egfl7 gene in malignant glioma. We found that the encoded extracellular matrix protein epidermal growth factor-like protein 7 (EGFL7) was secreted by glioma blood vessels but not glioma cells themselves, while no major role could be assigned to the parasitic miRNAs miR-126/126*. EGFL7 expression promoted glioma growth in experimental glioma models in vivo and stimulated tumor vascularization. Mechanistically, this was mediated by an upregulation of integrin α5β1 on the cellular surface of endothelial cells, which enhanced fibronectin-induced angiogenic sprouting. Glioma blood vessels that formed in vivo were more mature as determined by pericyte and smooth muscle cell coverage. Furthermore, these vessels were less leaky as measured by magnetic resonance imaging of extravasating contrast agent. EGFL7-inhibition using a specific blocking antibody reduced the vascularization of experimental gliomas and increased the life span of treated animals, in particular in combination with anti-VEGF and the chemotherapeutic agent temozolomide. Data allow for the conclusion that this combinatorial regimen may serve as a novel treatment option for GBM.
EVALuna2:212698

Genomic EWSR1 Fusion Sequence as Highly Sensitive and Dynamic Plasma Tumor Marker in Ewing Sarcoma - Krumbholz, Manuela; Hellberg, Julia; Steif, Benedikt; Bäuerle, Tobias; Gillmann, Clarissa; Fritscher, Torsten; Agaimy, Abbas; Frey, Benjamin; Juengert, Joerg; Wardelmann, Eva; Hartmann, Wolfgang; Juergens, Heribert; et al. (Clinical Cancer Research, 2016)
The application of the tumor-specific genomic fusion sequence as noninvasive biomarker for therapy monitoring in Ewing sarcoma (EwS) has been evaluated.EwS xenograft mouse models were used to explore detectability in small plasma volumes and correlation of genomic EWSR1-FLI1 copy numbers with tumor burden. Furthermore, 234 blood samples from 20 EwS patients were analyzed before and during multimodal treatment. EWSR1 fusion sequence levels in patients' plasma were quantified using droplet digital PCR and compared with tumor volumes calculated from MRI or CT imaging studies.Kinetics of EWSR1 fusion sequence copy numbers in the plasma are correlated with changes of the tumor volume in patients with localized and metastatic disease. The majority of patients showed a fast reduction of cell-free tumor DNA (ctDNA) during initial chemotherapy. Recurrence of increasing ctDNA levels signalized relapse development.Genomic fusion sequences represent promising noninvasive biomarkers for improved therapy monitoring in EwS. Until now, response assessment is largely based on MRI and CT imaging, implying restrictions on closely repeated performance and limitations on the differentiation between vital tumor and reactive stromal tissue. Particularly in patients with prognostic unfavorable disseminated disease, ctDNA is a valuable addition for the assessment of therapy response. Clin Cancer Res; 22(17); 4356-65. ©2016 AACR.
EVALuna2:6851

?-Synuclein-induced myelination deficit defines a novel interventional target for multiple system atrophy - Ettle, Benjamin; Kerman, Bilal E.; Valera, Elvira; Gillmann, Clarissa; Schlachetzki, Johannes; Reiprich, Simone; Büttner, Christian; Ekici, Arif Bülent; Reis, André; Wegner, Michael; Bäuerle, Tobias; Riemenschneider, Markus J.; et al. (Acta Neuropathologica, 2016)
Multiple system atrophy (MSA) is a rare atypical parkinsonian disorder characterized by a rapidly progressing clinical course and at present without any efficient therapy. Neuropathologically, myelin loss and neurodegeneration are associated with ?-synuclein accumulation in oligodendrocytes, but underlying pathomechanisms are poorly understood. Here, we analyzed the impact of oligodendrocytic ?-synuclein on the formation of myelin sheaths to define a potential interventional target for MSA. Post-mortem analyses of MSA patients and controls were performed to quantify myelin and oligodendrocyte numbers. As pre-clinical models, we used transgenic MSA mice, a myelinating stem cell-derived oligodendrocyte-neuron co-culture, and primary oligodendrocytes to determine functional consequences of oligodendrocytic ?-synuclein overexpression on myelination. We detected myelin loss accompanied by preserved or even increased numbers of oligodendrocytes in post-mortem MSA brains or transgenic mouse forebrains, respectively, indicating an oligodendrocytic dysfunction in myelin formation. Corroborating this observation, overexpression of ?-synuclein in primary and stem cell-derived oligodendrocytes severely impaired myelin formation, defining a novel ?-synuclein-linked pathomechanism in MSA. We used the pro-myelinating activity of the muscarinic acetylcholine receptor antagonist benztropine to analyze the reversibility of the myelination deficit. Transcriptome profiling of primary pre-myelinating oligodendrocytes demonstrated that benztropine readjusts myelination-related processes such as cholesterol and membrane biogenesis, being compromised by oligodendrocytic ?-synuclein. Additionally, benztropine restored the ?-synuclein-induced myelination deficit of stem cell-derived oligodendrocytes. Strikingly, benztropine also ameliorated the myelin deficit in transgenic MSA mice, resulting in a prevention of neuronal cell loss. In conclusion, this study defines the ?-synuclein-induced myelination deficit as a novel and crucial pathomechanism in MSA. Importantly, the reversible nature of this oligodendrocytic dysfunction opens a novel avenue for an intervention in MSA.
EVALuna2:4991

Temporal lobe reactions after carbon ion radiation therapy: comparison of relative biological effectiveness-weighted tolerance doses predicted by local effect models I and IV - Gillmann, Clarissa; Jäkel, Oliver; Schlampp, Ingmar; Karger, Christian P. (International Journal of Radiation Oncology Biology Physics, 2014)
To compare the relative biological effectiveness (RBE)-weighted tolerance doses for temporal lobe reactions after carbon ion radiation therapy using 2 different versions of the local effect model (LEM I vs LEM IV) for the same patient collective under identical conditions.In a previous study, 59 patients were investigated, of whom 10 experienced temporal lobe reactions (TLR) after carbon ion radiation therapy for low-grade skull-base chordoma and chondrosarcoma at Helmholtzzentrum für Schwerionenforschung (GSI) in Darmstadt, Germany in 2002 and 2003. TLR were detected as visible contrast enhancements on T1-weighted MRI images within a median follow-up time of 2.5 years. Although the derived RBE-weighted temporal lobe doses were based on the clinically applied LEM I, we have now recalculated the RBE-weighted dose distributions using LEM IV and derived dose-response curves with Dmax,V-1 cm³ (the RBE-weighted maximum dose in the remaining temporal lobe volume, excluding the volume of 1 cm³ with the highest dose) as an independent dosimetric variable. The resulting RBE-weighted tolerance doses were compared with those of the previous study to assess the clinical impact of LEM IV relative to LEM I.The dose-response curve of LEM IV is shifted toward higher values compared to that of LEM I. The RBE-weighted tolerance dose for a 5% complication probability (TD5) increases from 68.8 ± 3.3 to 78.3 ± 4.3 Gy (RBE) for LEM IV as compared to LEM I.LEM IV predicts a clinically significant increase of the RBE-weighted tolerance doses for the temporal lobe as compared to the currently applied LEM I. The limited available photon data do not allow a final conclusion as to whether RBE predictions of LEM I or LEM IV better fit better clinical experience in photon therapy. The decision about a future clinical application of LEM IV therefore requires additional analysis of temporal lobe reactions in a comparable photon-treated collective using the same dosimetric variable as in the present study.
EVALuna2:14518

Tumor Blood Vessel Visualization - Gillmann, Clarissa; Bäuerle, Tobias (Methods in Molecular Biology, 2016)
Noninvasive multimodal imaging of tumor blood vessels allows the qualitative and quantitative assessment of morphological, functional, and molecular features of tumor angiogenesis longitudinally in a living organism. In this chapter we focus on the application of magnetic resonance imaging (MRI), computed tomography (CT), ultrasound (US), and positron emission tomography (PET) in tumor blood vessel visualization on the example of breast cancer bone metastasis in a nude rat model. Thereby, materials and methods are described that are needed to obtain complementary data on tumor vascularization from these imaging techniques.
EVALuna2:14625

Ultra-high field MRI of human hippocampi: Morphological and multiparametric differentiation of hippocampal sclerosis subtypes - Gillmann, Clarissa; Coras, Roland; Roessler, Karl; Dörfler, Arnd; Uder, Michael; Blümcke, Ingmar; Bäuerle, Tobias (PLoS ONE, 2018)
The aim of the present study is to differentiate subtypes of hippocampal sclerosis (HS) using ex vivo ultra-high field magnetic resonance imaging (MRI). Included were 14 surgically resected hippocampi of patients with medically intractable temporal lobe epilepsy. The resected hippocampi were histologically categorized into subtypes of hippocampal sclerosis (HS type 1 (n = 10), HS type 2 (n = 2) and no-HS (n = 2)) and subsequently scanned on a preclinical 7T MRI acquiring T2-weighted morphology, relaxometry and diffusion tensor imaging. On the morphological images, the pyramidal cell layer (PCL) of the hippocampus was segmented and the following parameters were derived: T2 signal intensity, T1-, T2- and T2*-relaxation times, apparent diffusion coefficient (ADC), fractional anisotropy (FA) and mean diffusivity (MD). Furthermore, the area of the PCL was determined, as well as the parameter product which refers to the widths of the PCL parallel and perpendicular to the stratum moleculare. Spearman correlation coefficient was used to demonstrate relationships between MR-parameters and type of sclerosis. In comparison to no-HS specimens, the PCL was significantly narrower in HS type 1 and HS type 2 hippocampi. This narrowing affected the entire cornu ammonis sector (CA) 1 in HS type 1, while it was limited to the upper half of CA1 in direction to CA2 in HS type 2. The parameter product median increased from 0.43 to 1.67 and 2.91 mm2 for HS type 1, HS type 2 and no-HS, respectively. Correlation coefficients were significant for the PCL parameters product (0.73), area (0.71), T2*-time (-0.67), FA (0.65) and ADC (0.55). Our initial results suggest that HS type 1, HS type 2 and no-HS subtypes can be distinguished from each other using ex vivo UHF MRI based on T2-weighted morphologic images and the assessment of the parameter product. Upon clinical translation, UHF-MRI may provide a promising technique for the preoperative differentiation of HS subtypes in patients.
EVALuna2:34592